2021
DOI: 10.1101/2021.05.31.446354
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resurrected Rubisco suggests uniform carbon isotope signatures over geologic time

Abstract: Uniformitarian assumptions underlie the oldest evidence for living organisms on Earth, the distinct isotope fractionation between inorganic and organic carbon. Aside from a handful of compelling deviations, the 13C/12C isotopic mean of preserved organic carbon (δ13Corg) has remained remarkably unchanged through time. RuBisCO is the principal carboxylase/oxygenase biomolecular component that is thought to primarily account for the generation of these distinct carbon isotopic signals. However, it is difficult to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 91 publications
(157 reference statements)
1
12
1
Order By: Relevance
“…Prior studies also worked to account for issues related to growth physiology— specifically growth rate, cell shape and size— to adapt the C3 plant model to unicellular algae (25). However, that landmark study measured ε p in wild-type Cyanobacteria—the same wild-type strain studied here—and, unlike this study and (39), found ε p to be roughly constant independent of environmental pCO 2 and growth rate. Popp and coauthors hypothesized that this observed independence stems from the large surface area to volume ratio (SA/V) of Cyanobacteria, which was taken to imply much faster passive CO 2 uptake (scaling with SA) than fixation (scaling with V).…”
Section: Resultscontrasting
confidence: 80%
See 2 more Smart Citations
“…Prior studies also worked to account for issues related to growth physiology— specifically growth rate, cell shape and size— to adapt the C3 plant model to unicellular algae (25). However, that landmark study measured ε p in wild-type Cyanobacteria—the same wild-type strain studied here—and, unlike this study and (39), found ε p to be roughly constant independent of environmental pCO 2 and growth rate. Popp and coauthors hypothesized that this observed independence stems from the large surface area to volume ratio (SA/V) of Cyanobacteria, which was taken to imply much faster passive CO 2 uptake (scaling with SA) than fixation (scaling with V).…”
Section: Resultscontrasting
confidence: 80%
“…This suggested that CO2 availability is a growth-limiting factor for ANC but not WT, and further suggested that the differences in their growth kinetics are related to the efficacy of their CCMs. Consistent with our results, a similar ancestral Form 1B analogue displayed total carboxylase activity roughly half that of the modern Form 1B (39).…”
Section: Ancestral Rubisco Strain Grows At Ambient Co2 Concentrationssupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, recent studies that support the role of contingency in evolution might be explained by the specificity of mutation effects, adaptive landscape topography or environmental context (Kędzior et al. 2021; Xie et al. 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The resurrection strategy leveraged here importantly provides a means to directly test paradigms of early protein and metabolic evolution, including those associated with the emergence, robustness, and malleability of protein functionality (6, 7, 40-42), the development of protein-protein interactions and complexes (9-11), and the role of evolutionary contingency (43-45). Nevertheless, the experimental application of ancestral sequence resurrection toward the systems-level investigation of earliest evolved, biogeochemically crucial metabolic pathways remains in its infancy, despite the potential for provocative connections between molecular-scale innovations, planetary-scale evolution, and independent, geological records of life (46, 47).…”
Section: Discussionmentioning
confidence: 99%